Practice of Buying Jellyfish in Improving the Economy of Fisherman Communities - Simbra, Siti; Yatima, Khusnul; Puspitasari, Riska (Zabags International Journal of Economy, 2024)
The appearance of jellyfish in Air Hitam Laut Village, Sadu District, East Tanjung Jabung Regency, is an opportunity to improve the community's economy, especially jellyfish fishermen. The aim of this research is to find out how the process of buying and selling jellyfish improves the economy of the fishing community in Air Hitam Laut village, Sadu district, East Tanjung Jabung district. This research uses qualitative research methods, the subjects of this research are the fishing community in Air Hitam Laut village, Sadu sub-district, East Tanjung Jabung district. The data collection techniques are observation, interviews and documentation. The results of the research show that the sale and purchase of jellyfish has improved the economy of fishermen in the village of Air Hitam Laut, Sadu sub-district, East Tanjung Jabung regency. In the past, fishermen only focused on looking for fish and shrimp and if the net or fish catcher found jellyfish, they only threw them away, which is different from now with the business of buying and selling jellyfish, fishermen can sell jellyfish if the fisherman gets jellyfish while looking for fish.